Hubungan perilaku hidup sehat dengan distres psikologis pada mahasiswa keperawatan - Metty Wuisang; Ferdy Lainsamputty (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: Healthy lifestyle is very important to implement in order to prevent the occurrence of various diseases. Psychological distress is a negative mental health condition that can affect individuals either directly or indirectly. Changing lifestyle in a positive direction can prevent physical and mental disorders. Poor lifestyles and high levels of stress are common in nursing students.Purpose: To examine the relationship between healthy living behaviors and psychological distress among nursing students.Method: This study employed an analytic observational design with the cross-sectional method. A total of 169 samples were recruited using a consecutive sampling technique. A self-develop instrument and The General Health Questionnaire 12 (GHQ-12) were used to collect the data. Descriptive statistics and the Spearman correlation test were performed to determine the relationship.Results: Healthy living behaviors had a significant and negative relationship with psychological distress (r = -0.37; p<0.001).Conclusion: Nursing students who adopted healthier lifestyles, experienced lower psychological distress.Keywords: Healthy Lifestyle; Psychological Distress; Nursing StudentsPendahuluan: Perilaku hidup sehat sangat penting untuk diterapkan guna mencegah terjadinya berbagai penyakit. Distres psikologis merupakan suatu keadaan kesehatan mental negatif yang dapat mempengaruhi individu baik secara langsung maupun tidak langsung. Perilaku hidup sehat yang buruk dan tingkat stres yang tinggi sering terjadi pada mahasiswa keperawatan.Tujuan: Untuk mengetahui hubungan antara perilaku hidup sehat dengan distres psikologis pada mahasiswa keperawatan.Metode: Penelitian ini berjenis penelitian observasional analitik dengan metode potong lintang. Sejumlah 169 sampel direkrut menggunakan teknik consecutive sampling. Kuesioner yang dikembangkan oleh peneliti dan The General Health Questionnaire 12 (GHQ-12) digunakan dalam pengambilan data. Statistik deskriptif dan uji korelasi Spearman difungsikan untuk menentukan hubungan.Hasil: Perilaku hidup sehat dan distres psikologis mempunyai hubungan negatif yang signifikan (r = -0,37; p<0.001).Simpulan: Mahasiswa keperawatan yang menerapkan perilaku hidup yang lebih sehat, mengalami tekanan psikologis yang lebih rendah.